2016
DOI: 10.1186/s41118-016-0013-z
|View full text |Cite
|
Sign up to set email alerts
|

Bio-demographic factors affecting child loss in Tanzania

Abstract: The Republic of Tanzania has been experiencing one of the highest infant and child mortality rates. There have been few efforts in understanding the bio-demographic factors associated with child loss. The 2011-2012 Tanzania HIV/AIDS and Malaria Indicator Survey is the third comprehensive survey on HIV/AIDS carried out in Tanzania. This study employed logistic regression ratios to estimate the effects of key bio-demographic variables on the outcome variable (child loss). Children who belonged to mothers with pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…A similar study performed by Nasejje et al in 2015 11 further suggested that being a male child, female-headed household and number of births (one or more births) were significantly related to mortality in children <5 y of age in Uganda. A cross-sectional study conducted in Tanzania by Susuman et al 12 on the effect of biodemographic factors on child mortality indicated that birth interval and maternal parity (at least 4) were associated with deaths of children <5 y of age. Additionally, a community-based cross-sectional study on mortality in children <5 y of age in Abim district, Uganda showed that younger mothers (<20 y of age), previous birth interval (<2 y) and access to borehole water were significantly associated with the death of children <5 y of age.…”
Section: Introductionmentioning
confidence: 99%
“…A similar study performed by Nasejje et al in 2015 11 further suggested that being a male child, female-headed household and number of births (one or more births) were significantly related to mortality in children <5 y of age in Uganda. A cross-sectional study conducted in Tanzania by Susuman et al 12 on the effect of biodemographic factors on child mortality indicated that birth interval and maternal parity (at least 4) were associated with deaths of children <5 y of age. Additionally, a community-based cross-sectional study on mortality in children <5 y of age in Abim district, Uganda showed that younger mothers (<20 y of age), previous birth interval (<2 y) and access to borehole water were significantly associated with the death of children <5 y of age.…”
Section: Introductionmentioning
confidence: 99%